An Evaluating M-Banking Service Quality To Strengthen Loyalty And Satisfaction Of Customers Priority In The Digital Era - Rezki Rifai; Syafrizal; Sari Lenggogeni (Jurnal Mantik, 2022)
In this decade, mobile banking applications greatly facilitate customers to make transactions and enjoying banking services without having to visit branch offices, in which it can conducted anywhere. This paper aims to evaluate the direct and indirect effect of m-banking service quality on customer loyalty through mediating contribution of customer satisfaction. For the technique of sampling, this paper has used purposive with two criteria. In the distribution process, online method by assisting g-form questionnaires. As many as 154 completes questionnaires returned, then analyzed by Smart PLS 4.0.9 with the technique of SEM. Results indicated that M-banking service quality has a positive and significant effects on customer loyalty and satisfaction, then success in the mediating test by partial effect.